Implementasi Metode Simple Additive Weighting Untuk Penerimaan Mahasiwa Baru Jalur KIP Pada STMIK Dharma Wacana - Cici Novita Sari; Tri Aristi Saputri (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2023)
KIP scholarships at stmik have 7 (seven) types of scholarships given to prospective students such as KIP scholarships, achievement scholarships, Islamic boarding schools, CSR, DT Cares, Creator Content, and Tahfhidz Qur'an,There are registration problems and limited quotas, so it is necessary to have a selection of calculations and election data collection in order to produce accurate data. Of the several types of scholarships, the KIP scholarship is the scholarship most in demand by prospective STMIK Dharma Wacana students. Therefore, this research will focus on KIP scholarships. The method used for this problem is Simple Additive Weighting (SAW). The SAW method is expected to be able to select the best alternative from a number of alternatives.The criteria for accepting registration for prospective new students through the KIP route include: Written Test, Interview Test, Report Card Score Test, File Completeness Score, and Home Eligibility Value. The result of calculating the Simple Additive Weighting method is that the highest score is Ar-Roqiib'u Raihannicko, the second highest is Eka Diana Forensia, and the third highest is Ahmad Rendi Ardiyanto.